The role of SIRT1 in the development of gastrointestinal tumors - Zhang, Yueming; Zhou, Xiaokai; Zhai, Jinghui; Ma, Jie; Zhang, Sixi (Frontiers in Cell and Developmental Biology, 2025)
Gastrointestinal tumors, including esophageal cancer (EC), gastric cancer (GC) and colorectal cancer (CRC) and, pose significant global health challenges due to their high morbidity and mortality rates. SIRT1, an NAD+-dependent deacetylase, plays diverse roles in physiological processes and has been implicated in cancer development. This review examines the dual roles of SIRT1 in gastrointestinal tumors. In EC, SIRT1 consistently promotes tumor progression, with high SIRT1 expression associated with advanced TNM stage, poor prognosis, lymph node metastasis, and inferior overall survival. In GC, SIRT1 similarly promotes tumor progression via autophagy and chemoresistance, but studies also highlight its potential anti-cancer effects through ferroptosis regulation. In CRC, SIRT1 is often overexpressed and promotes tumor progression through mechanisms involving p53 inhibition, activation of the Wnt/β-catenin pathway, and regulation of Epithelial-Mesenchymal Transition (EMT). However, conflicting evidence suggests SIRT1 can also act as a tumor suppressor by inhibiting β-catenin and nuclear factor-κB (NF-κB) signaling. The dual nature of SIRT1 underscores the need for context-specific understanding of its function. Future research should focus on elucidating SIRT1’s mechanisms and developing personalized therapeutic strategies targeting SIRT1.